Reasons for the enhanced phase stability of Ru-containing nickel-based superalloys - Heckl, Astrid; Neumeier, Steffen; Cenanovic, S.; Göken, Mathias; Singer, Robert (Acta Materialia, 2011)
Improvements in phase stability on the addition of Ru are well known in the field of nickel-based superalloy development. However, the key mechanism of this benefit remains unclear. A new alloy series with stepwise increased additions of Ru was used to systematically investigate the impact of Ru on yopologically close-packed (TCP) phase inhibition. In addition, the investigation was carried out on a less known type of TCP formation, the so-called discontinuous precipitation. This type of TCP phase formation offers two major advantages compared with commonly investigated TCP plates in dendritic regions. First, the microstructure is much coarser than fine TCP plates, allowing reliable and less time consuming investigations. Second, discontinuous precipitation transforms the supersaturated and unstable γ/γ′ microstructure in a condition close to equilibrium, permitting a meaningful insight into the stable alloy constitution. The experimental results for alloy phase stability dependence on Ru are evaluated with respect to all possible effects of TCP phase inhibition by Ru. Furthermore, experimental evidence for increased Re solubility in the γ matrix was found on addition of Ru, which is not seen in corresponding ThermoCalc calculations. This finding is probably the dominant reason for the increased TCP phase capability of Ru-containing alloys. A ternary phase diagram model has been developed to describe the new approach. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Discontinuous precipitation; Phase stability; Ruthenium; ThermoCalc; Topologically close-packed phase inhibition